Asymmetric Capital Tax Competition with Profit Shifting - Sven Stöwhase (Ludwig-Maximilians-Universität München, Volkswirtschaftliche Fakultät, 2004)
This paper analyses capital tax competition between jurisdictions of different size when multinational firms can shift some fraction of their tax base between them. For the case of revenue maximizing governments, we show that introducing profit shifting will not generally increase downward pressure on tax rates. We find that profit shifting decreases the tax-base elasticity of the low tax jurisdiction while increasing the elasticity of the high tax jurisdiction. Therefore, by the direct (impact) effect, tax rates will converge as a result of additional profit shifting opportunities. In general equilibrium, however, tax rates may decrease or increase in both jurisdictions.
urn:nbn:de:bvb:19-epub-454-3
Keywords: F23; H25; H26; H32; 330; tax competition; asymmetric countries; profit shifting; multinational enterprises